Lithium secondary battery and manufacturing method
By using a lithium buffer layer and porous structure on the lithium metal anode, combined with the application of compressive stress, the problem of dendrites on the surface of the lithium metal anode is solved, and the effect of extending battery life and stable performance is achieved.
Patent Information
- Application Number
- CN202210204911.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-01
- Filing Date
- 2022-03-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-03-03
AI Technical Summary
Dental growth on the surface of lithium metal anode causes degeneration of battery cells, and the prior art is difficult to effectively control dendrite growth, resulting in a shortening of battery life.
The lithium buffer layer and porous structure are used on the lithium metal anode to control the conduction and deposition of lithium ions by applying compressive stress to prevent dendrites from growing.
Effectively control dendrites' growth, extend battery life, maintain stable charging/discharge performance, and reduce overall battery volume changes.
Smart Images

Figure CN115020644B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 156,079, filed on March 3, 2021, entitled “CONTROLLING LITHIUM PLATING BY LITHIUM-CONDUCTING BUFFER AND POROUS ANODE SCAFFOLD,” which is incorporated herein by reference in its entirety. Background Art
[0003] In a typical solid-state lithium-ion battery, the anode and cathode are separated by a solid electrolyte. During the battery's charge and discharge, lithium ions travel within the electrolyte between the anode and cathode.
[0004] It is well known that the use of lithium metal anodes in battery cells causes dendrite growth at the anode surface as the battery cell undergoes multiple charge / discharge cycles and / or high-rate charge / discharge events. Dendrite growth causes micro-shorts between the cathode and the anode, resulting in degradation of the battery cell.
[0005] Therefore, there is a need in the art for an improved rechargeable lithium battery cell that effectively controls dendrite growth on the surface of the lithium metal anode, thereby extending the life of the battery.
[0006] However, in view of the technology considered as a whole when making the present invention, it is not obvious to a person skilled in the art how to overcome the shortcomings of the prior art.
[0007] Although certain aspects of conventional technology have been discussed to facilitate the disclosure of the present invention, the applicant in no way denies these aspects of technology and contemplates that the claimed invention may encompass one or more of the conventional technology aspects discussed herein.
[0008] The present invention may solve one or more of the problems and deficiencies of the prior art discussed above. However, it is contemplated that the present invention may prove useful in solving other problems and deficiencies in many technical fields. Therefore, the claimed invention should not be construed as limited to solving any of the specific problems or deficiencies discussed herein.
[0009] In this specification, if a document, act or item of knowledge is referred to or discussed, such reference or discussion does not constitute an admission that the document, act or item of knowledge or any combination thereof constituted prior art at the priority date, was publicly available, was known to the public, was part of the common general knowledge, or otherwise constituted prior art under applicable legal provisions; or was known to be relevant to attempts to solve any problem addressed in this specification. Summary of the invention
[0010] In various embodiments, the present invention provides an improved secondary (rechargeable) lithium metal battery that exhibits stable charge / discharge performance and controlled volume change during charging and discharging of the battery.
[0011] In one embodiment, the rechargeable battery of the present invention comprises a solid electrolyte. In additional embodiments, the rechargeable battery cell comprises a hybrid electrolyte comprising a mixture of liquid and solid electrolytes.
[0012] In a specific embodiment, a lithium secondary battery is provided, comprising a lithium (Li) metal anode, a cathode layer, and a Li ion electrolyte layer positioned between the Li metal anode and the cathode layer. The battery further comprises a Li buffer layer compressed between the Li metal anode and the Li ion electrolyte layer, an anode collector, and a porous layer positioned between the Li metal anode and the anode collector. At a pressure of at least 0.1 MPa (megapascals), the Li buffer layer is compressed between the Li metal anode and the electrolyte layer to maintain the porosity of the porous layer.
[0013] The cathode layer may further include a cathode current collector and a cathode active material positioned between the cathode current collector and the electrolyte layer.
[0014] In a specific embodiment, the cathode active material may include LiNi in a weight ratio of 70:5:25, respectively. 0.6 Mn 0.2 Co 0.2 O2 (NMC) powder, carbon black conductive additive and lithium phosphate sulfur chloride (Li6PS5Cl) powder.
[0015] In general, the Li buffer layer provides high Li ion conductivity and low electrical conductivity, and the Li buffer layer has a lower Li ion conductivity than the electrolyte layer. In particular, the Li buffer layer may include lithium and one or more lithium compounds (LiX) selected from lithium chloride (LiCl), lithium fluoride (LiF), lithium bromide (LiBr) and lithium iodide (LiI). In a specific embodiment, the concentration of the lithium compound in the Li buffer layer may be between about 10 mol% and about 70 mol%, preferably between about 30 mol% and about 50 mol%. In an additional embodiment, the Li buffer layer may further include a composite comprising a solid electrolyte (SE) and one or more lithium compounds (LiX) selected from lithium chloride (LiCl), lithium fluoride (LiF), lithium bromide (LiBr) and lithium iodide (LiI).
[0016] As one embodiment, the electrolyte layer may be a solid Li-ion electrolyte. In particular, the electrolyte layer may be composed of lithium sulfur phosphate chloride (Li6PS5Cl) powder. In an alternative embodiment, the electrolyte layer may be a hybrid electrolyte comprising a mixture of liquid and solid Li-ion electrolytes.
[0017] The porous layer includes at least one mixed ion-electron conductor, and in particular, the porous layer may include Li 6.4 Ga 0.2 La3Zr2O 12 (LLZO) and carbon fiber.
[0018] Although various methods and techniques may be used in the manufacture of the above-mentioned lithium secondary batteries, in a specific embodiment, a method for manufacturing a lithium secondary battery may include: providing a cathode layer; positioning an electrolyte adjacent to the cathode layer; positioning a Li buffer layer adjacent to the electrolyte layer; establishing a compressive stress between the Li buffer layer and the electrolyte layer; positioning a Li metal anode layer on the Li buffer layer; positioning a porous layer on the Li metal anode layer; and positioning an anode collector on the porous layer.
[0019] Various embodiments of the present invention provide for the use of lithium metal anodes in lithium secondary (rechargeable) batteries, which significantly improves the volumetric and gravimetric capacity of the battery. The embodiments also prevent inherent problems common in battery cells utilizing lithium metal anodes, such as dendrite formation and large volume changes during charge / discharge cycles.
[0020] These embodiments are suitable for use in numerous areas where rechargeable batteries are needed, including but not limited to electric vehicles, portable electronic devices, and various other applications requiring high capacity, long cycle life, and minimal volume change during charge / discharge cycles.
[0021] Therefore, the present invention provides an improved rechargeable lithium battery that uses a Li buffer layer and a porous structure at the Li metal anode to effectively control the growth of dendrites on the surface of the lithium metal anode and alleviate the overall volume change of the battery, thereby extending the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] For a more complete understanding of the present invention, reference should be made to the following detailed description in conjunction with the accompanying drawings, in which:
[0023] Figure 1A A lithium secondary battery is shown during a charging cycle of the battery according to an embodiment of the present invention.
[0024] Figure 1B The present invention shows an embodiment of the battery during the discharge cycle Figure 1A of lithium secondary batteries.
[0025] Figure 2 is a graphical illustration of changes in the retention rate of conductivity relative to 0 mol % LiX with respect to the concentration (mol) of LiX in the Li buffer layer according to an embodiment of the lithium secondary battery of the present invention.
[0026] Figure 3 is a graphical illustration of battery voltage (V) during cycle 1 with respect to capacity of a first exemplary lithium secondary battery according to an embodiment of the present invention.
[0027] Figure 4 is a graphical illustration of battery voltage (V) relative to capacity of a first exemplary lithium secondary battery and a second exemplary lithium secondary battery during a 2nd cycle and a 3rd cycle according to an embodiment of the present invention.
[0028] Figure 5 is a scanning electron microscope (SEM) cross-sectional view of a main structure of a porous layer of a lithium secondary battery according to an embodiment of the present invention.
[0029] Figure 6 is a graphical illustration of discharge capacity versus cycle number for a third exemplary lithium secondary battery according to an embodiment of the present invention. DETAILED DESCRIPTION
[0030] In the following detailed description of the preferred embodiment, reference is made to the accompanying drawings, which form a part of the embodiment, and in which are shown by way of illustration specific embodiments in which the invention may be practiced. It should be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the invention.
[0031] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.
[0032] In lithium metal batteries currently known in the art, a lithium metal anode is deposited on a current collector, resulting in a change in volume of the lithium metal anode and the entire battery cell, regardless of whether a lithium buffer layer is used on the lithium metal anode.
[0033] In various embodiments of the present invention, a porous structure and a lithium (Li) buffer layer constituting mixed ion-electron conductivity in the anode of a lithium secondary battery are combined under an applied compressive stress to form a lithium secondary battery of the present invention. The porous structure of the anode forms a scaffold structure at the lithium metal anode layer, which effectively guides lithium deposition to a specified area, i.e., pre-existing holes in the porous structure. Therefore, embodiments of the present invention allow the Li metal anode to be uniformly deposited using a Li buffer layer, and also provide a porous structure using a Li metal anode to reduce the total volume change of the battery.
[0034] Figure 1A A lithium secondary battery is shown during a charging cycle of the battery 100 according to an embodiment of the present invention. Figure 1B shows the discharge cycle of the battery 100 according to an embodiment of the present invention. Figure 1A of lithium secondary batteries.
[0035] like Figure 1A and Figure 1B As shown, the all-solid-state rechargeable (secondary) lithium battery 100 according to an embodiment of the present invention includes a cathode layer, which includes a cathode collector 105 and a cathode active material 110 positioned on the cathode collector 105. The cathode active material 110 can be selected from oxides, including but not limited to LiNi x Mn y Co z O2, LiCoO2, LiFePO4. Alternatively, the cathode active material 110 may be selected from other Li complexes, such as sulfides. In a specific embodiment, the cathode active material may include LiNi in a weight ratio of 70:5:25, respectively. 0.6 Mn 0.2 Co 0.2 O2 (NMC) powder, carbon black conductive aid, and lithium sulfur phosphate chloride (Li6PS5Cl) powder. However, this is not intended to be limiting, and various other compounds and ratios are within the scope of the present invention to provide the cathode active material 110.
[0036] The lithium secondary battery further includes a solid lithium ion electrolyte layer 115 positioned on the cathode active material 110, and a Li buffer layer 125 positioned on the solid lithium ion electrolyte layer 115. The lithium secondary battery further includes an anode layer, which includes a lithium metal anode 130 positioned on the Li buffer layer 125, a porous layer 135 located on the Li metal anode 130, and an anode collector 140 positioned on the porous layer 135. The Li buffer layer 125 is compressed between the Li metal anode 130 and the anode collector 140.
[0037] Generally, the Li buffer layer 125 provides high Li ion conductivity and low electrical conductivity. The Li buffer layer 125 may be composed of a lithium alloy with a concentration between 1% and 99%. Therefore, the Li buffer layer 125 provides ion conductivity and electronic insulation properties to suppress the formation of dendrites on the lithium metal anode 130, thereby preventing the formation of micro short circuits in the battery 100.
[0038] In a specific embodiment, the Li buffer layer 125 includes lithium and one or more lithium compounds (LiX). The lithium compound may include lithium chloride (LiCl), lithium fluoride (LiF), lithium bromide (LiBr), and lithium iodide (LiI). Table 1 shows the relationship between ionic conductivity and electrical conductivity based on the molar ratio between lithium and fluoride in the Li buffer layer 125.
[0039] Table I
[0040]
[0041] Figure 2 Graph 200 shows the change in the retention rate of the conductivity relative to 0 mol% LiX relative to the change in the concentration of LiX in the Li buffer layer 125. The ideal characteristic of the Li buffer layer 125 is to exhibit high ionic conductivity and low conductivity. Since LiX has a lower ionic conductivity than the solid lithium ion electrolyte layer 115, it is inevitable that the ionic conductivity of the Li buffer layer 125 decreases with the increase in the concentration of LiX. Therefore, it is appropriate to select a LiX concentration for the Li buffer layer 125 that can maintain high ionic conductivity while also providing a lower conductivity. Therefore, in a specific embodiment, the concentration of LiX in the Li buffer layer 125 is between about 10 mol% and about 70 mol%, and more particularly, between about 30 mol% and about 50 mol%.
[0042] in addition Figure 1A and Figure 1B , a soft solid electrolyte interface (SEI) 120 is shown, which is naturally formed between the solid lithium ion electrolyte layer 115 and the Li buffer layer 125 during the charge and discharge cycles of the battery 100. The soft SEI interface 120 is permeable to lithium ions and is also electrically insulating.
[0043] In certain embodiments, the anode collector 140 may be composed of one or more elements, including but not limited to nickel (Ni), copper (Cu), or stainless steel (SUS) compositions. The porous layer 135 may be composed of one or more mixed ionic electronic conductors. The lithium metal anode 130 may be composed of high-capacity lithium.
[0044] In the battery 100 of the present invention, compressive stress is established between the solid lithium ion electrolyte layer 115 and the Li buffer layer 125. In a specific embodiment, the compressive stress is between about 0.1 MPa and about 100 MPa.
[0045] In addition, Figure 1A As shown, the porous layer 135 includes a plurality of pores. Figure 1B As shown, during charging of the battery 100, the pores control the direction of lithium plating (deposition) by establishing compressive stress at the interface. In general, the porous layer 135 guides the location of lithium deposition at the Li metal anode 130, thereby reducing the volume change of the lithium metal anode 130 during the charge / discharge cycle by filling the pores of the porous layer 135. The introduction of the porous layer 135 controls and minimizes the change in the overall battery cell size, which contributes to the dimensional stability of the battery 100 when it is installed in electric vehicles (EVs) and hybrid electric vehicles (HEVs).
[0046] In order to confirm the effect of the Li buffer layer 125 in the battery 100 of the present invention, a particle-type solid-state battery was described and tested. In this exemplary embodiment, the cathode active material 110 is LiNi in a weight ratio of 70:5:25. 0.6 Mn 0.2 Co 0.2 O2 (NMC) powder, carbon black conductive aid and lithium sulfur phosphate chloride (Li6PS5Cl) powder, and 10 mg of the mixed powder was used as the cathode active material 110. The solid lithium ion electrolyte layer 115 was composed of lithium sulfur phosphate chloride (Li6PS5Cl) powder, of which 100 mg was used for the solid lithium ion electrolyte layer 115. For the Li metal anode 130, a 20 μm thick laminated foil and a 10 μm thick copper (Cu) were used.
[0047] The cathode active material 110, the solid lithium ion electrolyte layer 115 material and the Li metal anode 130 material are placed in a ceramic cylinder with an inner diameter of about 10 mm and compressed with a stainless steel cylinder to form a granular solid-state battery.
[0048] After forming the cathode active material layer, the Li buffer layer 125 was formed by compressing 5 mg of the powder mixture uniformly dispersed on the solid lithium ion electrolyte layer 115 under a pressure of 100 MPa. The all-solid-state battery was then compacted under a pressure of 400 MPa. The resulting battery prepared by the above process was then connected to a constant current charge / discharge test at 0.1 mA, with the upper and lower cut-off voltages being 4.3 V and 2.7 V, respectively. In addition, a compressive stress of 100 MPa was applied to the battery during the test. The test results are shown in Figure 3 and Figure 4 middle.
[0049] exist Figure 3 and Figure 4 , Example 1 310 represents a Li buffer layer 125 composed of 30 mol % LiF, Example 2 405 represents a Li buffer layer 125 composed of 50 mol % LiF, and Reference 1 305 represents a Li buffer layer 125 composed of 0 mol % LiF.
[0050] refer to Figure 3 , in the first cycle graph 300, Example 1 310 starts the first charge at about 3.5V. However, Reference 1 305 exhibits an abnormal reaction 315 at about 2.0V. As shown, the first cycle Coulombic efficiency of Example 1 310 is improved by 10% compared to Reference 1 305. Figure 4 In the graph 400 of the 2nd and 3rd cycles, Example 1 310 and Example 2 405 do not show significant capacity fade, at least until the 3rd cycle. However, Reference 1 305 shows a significant decrease in capacity in the 3rd cycle. Figure 3 and Figure 4 The results shown clearly demonstrate that the Li buffer layer 125 of Example 1 310 and Example 2 405 enables uniform reaction on the Li metal anode 130 of the cell 100, which is a desirable feature for a rechargeable Li cell.
[0051] An exemplary embodiment for manufacturing a battery including the porous layer 135 may involve the manufacture of a main structure. In an exemplary embodiment, the material of the structure may include an 8 μm thick copper foil as the cathode collector 105, vapor-grown carbon fibers as the main structure, polyvinylidene fluoride (PVdF) as a binder, and N-methylpyrrolidone (NMP) as a solvent to prepare a slurry having a composition shown in Table II below.
[0052] Table II
[0053] Binder solvent Mw: 6 wt% in 880000 NMP
[0054] Production batch number VGCF(g) Binder solvent (g) LLZO(g) NMP(g) Total (g) SuVG_1 1.5 3 0 40 44.5 SuVG_1 1.5 4.5 0 40 46 VGZ1_1 1.5 5 1 40 47.5 VGZ1_1 2.52 6.04 1 40 49.56
[0055] The slurry was uniformly mixed using a homogenizer at a speed of 1000 rpm for 3 hours at room temperature (25°C). The prepared slurry was applied to the copper foil using a rod coater with a 50 mil gap. After applying the slurry, the resulting electrode was dried at 120°C for 12 hours using a vacuum dryer. The dried electrode was then punched into a circular electrode with a diameter of 10 mm using a vacuum dryer and kept at 80°C for 24 hours, similar to the drying step described previously. In order to provide the compression properties of the structure, the above-mentioned main structure was clamped with a stainless steel mold, compressed at 0.1 MPa using a hydraulic press, and then the porosity was determined by structural analysis and the weight / thickness of the membrane. The pores present in the above-mentioned main structure of the porous layer 135 were confirmed by scanning electron microscopy. The scanning results are shown in Figure 5 middle.
[0056] An exemplary test cell was manufactured, which included a previously formed cathode layer, a solid lithium ion electrolyte layer 115, and a Li metal layer 130, with the above-described main structure at the top. These layers were stacked and bonded with compressive stress. In particular, the compressive pressure was controlled between about 0.1 MPa and about 10 MPa. However, in order to maintain the porosity in the porous layer 135, a lower pressure was required.
[0057] In order to verify the charge and discharge cycle results of the lithium secondary battery of the present invention, the exemplary test cell prepared by the above steps was connected to a constant potential instrument and a constant current charge and discharge test was performed at 0.1 mA, with the upper and lower cut-off voltages being 4.3 V and 2.8 V, respectively. Additionally, the battery cell was compressed at 0.1 MPa during the test to maintain the porosity of the porous layer 135. The results of the cycle test are shown in Figure 6 In. From Figure 6 As can be seen in the graph 600 , after 30 cycles, Example 3 605 including the porous layer 135 exhibits more than 10 times the capacity compared to the reference 1305 , which clearly shows that the cycle performance is improved by absorbing the volume change by the bulk layer of the porous layer 135 through the charge / discharge reaction.
[0058] The all-solid-state lithium secondary battery of the present invention provides uniform lithium deposition to prevent the formation of dendrites, while also enabling controlled growth of lithium in a specific direction and into a specified area of the battery cell. With these unique features, the battery cell will have a longer service life, with stable charge / discharge performance and controlled volume change of the battery cell.
[0059] While the illustrated embodiments relate to batteries comprising a solid electrolyte, this is not intended to be limiting and it is within the scope of the invention that the battery cells may alternatively comprise a hybrid electrolyte comprising a mixture of liquid and solid electrolytes.
[0060] The above advantages as well as those apparent from the foregoing description are efficiently obtained.As certain changes could be made in the above constructions without departing from the scope of the invention, it is intended that all matter contained in the foregoing description or shown in the accompanying drawings shall be interpreted as illustrative and not in a limiting sense.
[0061] It is also to be understood that the following claims are intended to cover all generic and specific features of the invention described herein, as well as all statements of the scope of the invention which, as a matter of language, might be said to fall therebetween.
Claims
1. A lithium secondary battery, comprising: Li metal anode layer; cathode layer; an electrolyte layer positioned between the Li metal anode layer and the cathode layer; A Li buffer layer, the Li buffer layer being compressed between the Li metal anode layer and the electrolyte layer; Anode collector; as well as a porous layer positioned between the Li metal anode layer and the anode collector, The Li buffer layer comprises lithium, a solid electrolyte and lithium fluoride, the molar number of lithium fluoride in the Li buffer layer accounts for between 10% and 70% of the sum of the molar number of lithium fluoride and the molar number of the solid electrolyte, and the Li buffer layer is compressed between the Li metal anode layer and the electrolyte layer at a pressure of at least 0.1 MPa, The porous layer contains Li 6.4 Ga 0.2 La3Zr2O 12 and carbon fiber.
2. The lithium secondary battery of claim 1, wherein the cathode layer comprises: cathode collector; as well as A cathode active material is positioned between the cathode current collector and the electrolyte layer.
3. The lithium secondary battery of claim 2, wherein the cathode active material comprises LiNi in a weight ratio of 70:5:
25. 0.6 Mn 0.2 Co 0.2 O2 powder, carbon black conductive additive and lithium phosphate sulfur chloride powder. 4 . The lithium secondary battery according to claim 1 , wherein the molar number of lithium fluoride in the Li buffer layer accounts for between 30% and 50% of the sum of the molar number of lithium fluoride and the molar number of the solid electrolyte. 5 . The lithium secondary battery as claimed in claim 1 , wherein the Li buffer layer has lower Li ion conductivity than the electrolyte layer. 6 . The lithium secondary battery as claimed in claim 1 , wherein the electrolyte layer is a solid Li ion electrolyte.
7. The lithium secondary battery of claim 1, wherein the electrolyte layer comprises lithium phosphate sulfur chloride powder. 8 . The lithium secondary battery of claim 1 , wherein the electrolyte layer is a mixed electrolyte comprising a mixture of liquid and solid Li ion electrolytes. 9 . The lithium secondary battery of claim 1 , wherein the Li metal anode layer comprises Li metal and copper.
10. A method for manufacturing a lithium secondary battery, the method comprising: providing a cathode layer; positioning an electrolyte layer adjacent to the cathode layer; positioning a Li buffer layer adjacent to the electrolyte layer; establishing a compressive stress between the Li buffer layer and the electrolyte layer; positioning a Li metal anode layer on the Li buffer layer; positioning a porous layer on the Li metal anode layer; and positioning an anode collector on the porous layer, The Li buffer layer comprises lithium, a solid electrolyte and lithium fluoride, wherein the molar number of lithium fluoride in the Li buffer layer accounts for between 10% and 70% of the sum of the molar number of lithium fluoride and the molar number of the solid electrolyte, The porous layer contains Li 6.4 Ga 0.2 La3Zr2O 12 and carbon fiber.
11. The method of claim 10, wherein the electrolyte layer comprises solid lithium sulfur chloride phosphate, and wherein the Li buffer layer has a lower Li ion conductivity than the electrolyte layer.
Citation Information
Patent Citations
Production method of lithium / carbon fiber or porous carbon paper / copper foil composite negative electrode used for lithium-sulfur battery
CN106711430A
Solid state batteries, SSE batteries, lithium metal batteries with solid state electrolytes, HSSE, separators, and / or coatings, and / or related methods
WO2019195553A1